Preparation and characterization of CuInSe2 thin films by chemical bath deposition technique - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Jadhav, A. V.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2010)
Copper indium diselenide (CIS) thin films have been deposited using a precursor solution containing copper sulphate, indium trichoride, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium at room temperature. The as grown brown colored films were found to be well adherent to glass substrates. The films were characterized by X-ray diffraction, scanning electron microscopy, atomic absorption spectroscopy, optical absorption, electrical resistivity, and thermo electric measurement techniques. The analysis of optical absorption data shows band-gap energy (E-g) to be 1.1 eV. The electrical resistivity of the thin film was found to be of the order of 10(2) (Omega cm). Thermoelectric power measurement shows n-type conduction. (C) 2010 Published by Elsevier B.V.
Keywords: CuInSe2; Optical properties; Thin films; X-ray diffraction

Photoelectrochemical applications of In2Se3 thin films by chemical deposition - Hankare, P. P.; Rathod, K. C.; Asabe, M. R.; Jadhav, A. V.; Helavi, V. B.; Chavan, Santosh S.; Garadkar, K. M.; Mulla, Imtiaz S. (Journal of Materials Science-Materials in Electronics, 2011)
Indium selenide films have been synthesized by chemical bath deposition method onto stainless steel plate. The configuration of fabricated cell is n-In2Se3| NaOH(1 M) + S(1 M) + Na2S(1 M) |C-(graphite). Characterization of the photoelectrochemical cell was carried out by studying X-ray diffraction, current-voltage and capacitance-voltage characteristics in the dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that the In2Se3 thin films are n-type semiconductor. The junction ideality factor was found to be 3.24. The flat band potential and the barrier height were found to be 0.720 V and 0.196 eV, respectively. From the study of power output characteristics, open circuit voltage, short circuit current, fill factor and efficiency were found to be 310 mV, 20 mu A, 37.64 and 0.61%, respectively. Photoresponse studies show that the lighted ideality factor is 2.78. Maximum current was observed at 575 nm.

Chemical deposition of CuInSe2 thin films by photoelectrochemical applications - Hankare, P. P.; Rathod, K. C.; Chate, P. A.; Garadkar, K. M.; Sathe, D. J.; Mulla, Imtiaz S. (Journal of Alloys and Compounds, 2012)
Copper indium diselenide films have been synthesized by chemical bath deposition method. The configuration of fabricated cell is n-CuInSe2|NaOH (1 M) + S (1 M) + Na2S (1 M)|C-(graphite). The photoelectrochemical cell characterization of the films is carried out by studying current-voltage characteristics in dark, capacitance-voltage in dark, barrier height measurements, power output, photoresponse and spectral response. The study shows that CuInSe2 thin films are n-type conductivity. The junction ideality factor is found to be 3.81. The flat band potential is found to be 0.763 V. The barrier height value is found to be 0.232 eV. The study of power output characteristic shows open circuit voltage, short circuit current, fill factor and efficiency are found to be 310 mV, 20 mu A, 42.12% and 0.82%, respectively. Photoresponse shows lighted ideality factor which is 2.92. Spectral response shows the maximum current observed at 650 nm. (C) 2011 Published by Elsevier B.V.
Keywords: Chemical bath deposition; Flat band potential; Photo response; Power output; Spectral response